(untitled) (Diversity Research: Journal of Analysis and Trends, 2026)
his cursory article analyses how metaphorical polysemy – one lexical form carrying several metaphor-related senses – creates humour in English and Russian. The core claim is functional: polysemous words become humorous when discourse lets two interpretations remain briefly plausible, so the recipient must reanalyse the utterance and notice the speaker’s “designed ambiguity.” Linguistically, this mechanism fits script-based accounts of humour, where a text becomes funny when it supports an opposition between compatible interpretive scripts (Raskin, 1985; Attardo & Raskin, 1991). At the processing level, graded salience research predicts that familiar metaphorical meanings may be activated alongside literal meanings, which makes double-access effects cognitively available for joking (Giora, 1997). Evidence from Russian ERP studies further indicates that metaphor-related senses can induce competition and reinterpretation during comprehension – an interpretable cognitive correlate of punchline-like reprocessing (Yurchenko et al., 2020). Culturally, metaphor repertoires and humour norms shape which polysemies are “safe,” recognizable, and translatable across English and Russian communities